SYNTHESIS, ELECTRONIC AND PHOTOPHYSICAL PROPERTIES OF 3,8-DIAROMATIC-1,10-PHENANTHROLINE MOLECULES - José Muñoz; Felipe Peñaloza; Kevin Guajardo; Roxana Arce; Nancy Pizarro; Andres Vega (Journal of the Chilean Chemical Society, 2025)
The molecules 3,8-diphenyl-1,10-phenanthroline (L1), 3,8-di(naphthalen-1-yl)-1,10-phenanthroline (L2), 3,8-di(naphthalen-2-yl)-1,10-phenanthroline (L3), 3,8-di(anthracen-9-yl)-1,10-phenanthroline (L4), and 3,8-di(pyren-1-yl)-1,10-phenanthroline (L5) were prepared in good yield from the reaction of 3,8-dibromo-1,10-phenanthroline with the corresponding boronic acid, catalysed by [Pd(PPh₃)₄]. Computational DFT modelling suggests that the aromatic substituent arms are not coplanar with the central phenanthroline (phen) core, and that the HOMO-LUMO gap diminishes as the number of fused carbon rings in the arms increases. Cyclic voltammograms for the ligands show between one and two oxidation and one to three reduction waves, which are believed to be centred on the arms and the central phen fragments, respectively, suggesting some small electronic mixing. The absorption and emission properties depend on the electronic interaction between the polyaromatic substituents and the phenanthroline core. Different emissive ππ* excited states for the molecules bearing anthryl and pyrenyl substituents suggest they have more charge transfer character, and a consequent sensitivity to the increase of solvent polarity. The photosensitizing capacity of singlet oxygen generation upon excitation of L1-L5 in solution is consistent with a significant evolution of the former singlet excited state towards a triplet excited state.